The signifi cance of the theory of evidence in criminal proceedings (Journal of actual problems of jurisprudence, 2019)
In this article, the author examines the general provisions on proof theory has developed in the modern science of criminalproceedings. The author makes an analysis on the current prevailing opinion on the evidence and facts.Keywords: evidence, criminal procedure, proof theory, solve the crime, exposing the criminal, the fact.